An integrated fingerprinting and kinetic approach to accelerated shelf-life testing of chemical changes in thermally treated carrot puree. (15th July 2015) - Kebede, Biniam T.; Grauwet, Tara; Magpusao, Johannes; Palmers, Stijn; Michiels, Chris; Hendrickx, Marc; Loey, Ann Van
Highlights: A fingerprinting-kinetics strategy enabled a better insight into shelf-life changes. The volatile fraction of sterilised carrot puree clearly changes during shelf-life. The amount of Strecker aldehydes increased during storage. Terpene, fatty acid derivatives and sulphur compounds decreased during storage. Abstract: To have a better understanding of chemical reactions during shelf-life, an integrated analytical and engineering toolbox: "fingerprinting-kinetics" was used. As a case study, a thermally sterilised carrot puree was selected. Sterilised purees were stored at four storage temperatures as a function of time. Fingerprinting enabled selection of volatiles clearly changing during shelf-life. Only these volatiles were identified and studied further. Next, kinetic modelling was performed to investigate the suitability of these volatiles as quality indices (markers) for accelerated shelf-life testing (ASLT). Fingerprinting enabled selection of terpenoids, phenylpropanoids, fatty acid derivatives, Strecker aldehydes and sulphur compounds as volatiles clearly changing during shelf-life. The amount of Strecker aldehydes increased during storage, whereas the rest of the volatiles decreased. Out of the volatiles, based on the applied kinetic modelling, myristicin, α-terpinolene, β-pinene, α-terpineol and octanal were identified as potential markers for ASLT.